(3GdCH GdKGdK h GdCWaGds (3GdCJLGgGJ GdMOjKI dJCKjQGJ GdJdjaRjhf Ydi GdCWaGd (B/s - (3eMeO eYhV (B.s; (3eMeO eYhV (B.s ((3GdbGgQI (B:s (3OGQ GdcJGH GdMOjK(B,s, 2000)
(3jJfGhd GdcJGH JCKQ GdCWaGd HGdKbGaGJ GdeNJdaI ef NdGd GdJdjaRjhf Hcd eG jJfGhdI ef KbGaGJ eNJdaI cGdCNHGQ h GdHQGeL GdJYdjejI h GdCYdGfGJ CjVG GdCadGe h GdOQGeG h GdYfa (B.s
(3GdJdjaRjhf h GdCWaGd (B.s
All age.
Keywords: (3GdJdjaRjhf (B- (3KbGaI(B.s -- (3CWaGd(B.s